Immigration and nationalism in the long run - Valentin Lang; Stephan A. Schneider (ETH Zurich, KOF Swiss Economic Institute, 2022)
During recent immigration waves, nationalist parties increased their vote shares in many countries, but the political backlash against immigration in some regions was much stronger than in others. We examine whether past experience with migrant inflows shapes voters' reactions to current immigration waves. Our study is based on a natural experiment from Germany, where a short-term and demonstrably arbitrary drawing of occupation zones entailed a discontinuous distribution of forced migrants after World War II. Combining historical migration and election records in a 1949-2021 panel at the municipality level, we exploit these differences in a spatial fuzzy regression discontinuity design. Our results show a substantially weaker nationalist backlash against current immigration in regions that received more forced migrants in the past. Current immigration levels activate and mute this effect of exposure to immigration in the past over a period of at least 70 years.
hdl:20.500.11850/569180
Keywords: D72; O15; 330; Migration; Nationalism; Persistence; Voting Behavior